2022
DOI: 10.3390/ijms23147995
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of NF-κB Signaling Molecules in Bone Metabolism Revealed by Genetic Mutations in Osteopetrosis

Abstract: The nuclear factor-κB (NF-κB) transcription factor family consists of five related proteins, RelA (p65), c-Rel, RelB, p50/p105 (NF-κB1), and p52/p100 (NF-κB2). These proteins are important not only for inflammation and the immune response but also for bone metabolism. Activation of NF-κB occurs via the classic and alternative pathways. Inflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin (IL)-1β, activate the former, and cytokines involved in lymph node formation, such as receptor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Long-term use of related drugs that inhibit osteoclast function and generation is relevant to all adverse effects (8, 38). For instance, anti-resorptive bisphosphonate drugs can effectively block the bone resorption function of osteoclasts but destroy the normal bone remodeling process causing mandibular osteonecrosis and atypical femur fractures (41,45,46). So, developing novel osteoporosis treatments in recent years has been desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of related drugs that inhibit osteoclast function and generation is relevant to all adverse effects (8, 38). For instance, anti-resorptive bisphosphonate drugs can effectively block the bone resorption function of osteoclasts but destroy the normal bone remodeling process causing mandibular osteonecrosis and atypical femur fractures (41,45,46). So, developing novel osteoporosis treatments in recent years has been desirable.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a redox-sensitive transcription factor. The activation of NF-κB signaling is regulated by the intracellular response to oxidative stress and inflammation [ 33 ]. NF-κB signaling transduction plays an important role in BMP-2 [ 34 ], IL-1β [ 35 ], IL-6 [ 36 ], and TNF-α [ 37 ] gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that both the IKKα and β subunits exhibit catalytic activity, while NEMO/IKKγ is involved in the recruitment of IκBs ( Barczewski et al, 2019 ). Moreover, IKKβ has been identified as the predominant kinase responsible for IκB phosphorylation ( Yamada et al, 2020 ; Jimi and Katagiri, 2022 ). The phosphorylation of IκBs triggers their polyubiquitination, proteasomal degradation by the 26s proteasome, and eventually the release of NF-κB transcription factor into the nucleus ( Chen and Greene, 2004 ).…”
Section: Genetic Basis Of the Eda/edar/nf-κb Signaling Pathwaymentioning
confidence: 99%
“…The phosphorylation of IκBs triggers their polyubiquitination, proteasomal degradation by the 26s proteasome, and eventually the release of NF-κB transcription factor into the nucleus ( Chen and Greene, 2004 ). NF-κB is a homo or heterodimer that can be formed from different combinations of RelA (p65), c-Rel, RelB, p50/p105 (NF-κB1), and p52/p100 (NF-κB2) ( Courtney et al, 2005 ; Yamada et al, 2020 ; Jimi and Katagiri, 2022 ). After the nuclear translocation of NF-κB, it induces the expression of genes essential for initiating and differentiating skin appendages such as hair, teeth, and sweat glands ( Figure 2 ).…”
Section: Genetic Basis Of the Eda/edar/nf-κb Signaling Pathwaymentioning
confidence: 99%